Uterine transplantation: legal and regulatory implications in England. (4th October 2021) - Vali, S; Jones, BP; Saso, S; Fertleman, M; Testa, G; Johanesson, L; Alghrani, A; Smith, JR
Abstract : Uterus transplantation (UTx) is fast evolving from an experimental to a clinical procedure, combining solid organ transplantation with assisted reproductive technology. The commencement of the first human uterus transplant trial in the United Kingdom leads us to examine and reflect upon the legal and regulatory aspects closely intertwined with UTx from the process of donation to potential implications for fertility treatment and the birth of the resultant child. As the world's first ephemeral transplant, the possibility of organ restitution requires consideration and is discussed herein. Tweetable abstract: Uterine transplantation warrants a closer look at the legal frameworks on fertility treatment and transplantation in England. Tweetable abstract: Uterine transplantation warrants a closer look at the legal frameworks on fertility treatment and transplantation in England.